Alterations of Endothelial Glycocalyx During Orthotopic Liver Transplantation in Patients With End-Stage Liver Disease. Issue 10 (October 2015) - Schiefer, Judith; Lebherz-Eichinger, Diana; Erdoes, Gabor; Berlakovich, Gabriela; Bacher, Andreas; Krenn, Claus G.; Faybik, Peter
<x xml:space="preserve">Abstract</x> Background Endothelial glycocalyx participates in the maintenance of vascular integrity, and its perturbations cause capillary leakage, loss of vascular responsiveness, and enhanced adhesion of leukocytes and platelets. We hypothesized that marked shedding of the glycocalyx core protein, syndecan-1, occurs in end-stage liver disease (ESLD) and that it increases during orthotopic liver transplantation (OLT). We further evaluated the effects of general anesthesia on glycocalyx shedding and its association with acute kidney injury (AKI) after OLT. Patients and Methods Thirty consecutive liver transplant recipients were enrolled in this prospective study. Ten healthy volunteers served as a control. Acute kidney injury was defined by Acute Kidney Injury Network criteria. Results Plasma syndecan-1 was significantly higher in ESLD patients than in healthy volunteers (74.3 ± 59.9 vs 10.7 ± 9.4 ng/mL), and it further increased significantly after reperfusion (74.3 ± 59.9 vs 312.6 ± 114.8 ng/mL). The type of general anesthesia had no significant effect on syndecan-1. Syndecan-1 was significantly higher during the entire study in patients with posttransplant AKI stage 2 or 3 compared to patients with AKI stage 0 or 1. The area under the curve of the receiver operating characteristics curve of syndecane-1 to predict AKI stage 2 or 3 within 48 hours after reperfusion was 0.76 (95% confidence interval, 0.57–0.89, P = 0.005). Conclusions Patients with ESLD suffer from glycocalyx alterations, and ischemia-reperfusion injury during OLT further exacerbates its damage. Despite a higher incidence of AKI in patients with elevated syndecan-1, it is not helpful to predict de novo AKI. Volatile anesthetics did not attenuate glycocalyx shedding in human OLT.